Perovskite nanoparticles : synthesis, properties, and novel applications in photovoltaics and LEDs - Kulkarni, Sneha Avinash (2020)
Solar cells and light-emitting diodes (LEDs) based on metal-halide perovskites are transitioning from promising performers to direct competitors to well-established technologies, with cost-effectiveness as a strong advantage. Nanostructured perovskites have yielded record LEDs due to their higher versatility in the local management of charge carriers, which has enabled photoluminescence quantum yields (PLQYs) close to 100%. However, these perovskite nanostructures are yet to be fully exploited in other applications such as photovoltaics, where they can also present competitive advantages as they enable feasible routes to surpass the Shockley–Queisser limit by means of multiexciton generation or hot-carrier extraction. Besides conventional applications, the extraordinary properties of these materials have the potential to unlock novel areas of research. Herein, the potential of perovskite nanostructures—with the focus on the widely developed nanoparticles—beyond classical thin-film optoelectronics is analyzed, their limits of application are discussed, and their real possibilities are pondered.